2021
DOI: 10.1094/pdis-01-21-0219-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report ofBotrytis cinereaCausing Gray Mold on Greenhouse-Grown Tomato Plants in Mauritius

Abstract: Gray mold is one of the most important fungal diseases of greenhouse-grown vegetables (Elad and Shtienberg 1995) and plants grown in open fields (Elad et al. 2007). Its etiological agent, Botrytis cinerea, has a wide host range of over 200 species (Williamson et al. 2007). Greenhouse production of tomato (Lycopersicon esculentum Mill.) is annually threatened by B. cinerea which significantly reduces the yield (Dik and Elad 1999). In August 2019, a disease survey was carried out in a tomato greenhouse cv. ‘Elpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…In this context, an early study by Dulymamode et al [18] reported that over 200 taxa were identified on the island, of which 90% were new records that had been assigned to one genus and 38 new species. However, studies that specifically focus on Fusarium species are severely lacking, with the only work being a 2023 study by Mamode Ally et al [19] who reported the first case of Fusarium acacia-mearnsii responsible for leaf blight in pumpkin in Mauritius. This highlights the need to undertake more research on the prevalence of Fusarium species in the country as an outbreak of Fusarium infection could have devastating consequences for Mauritius, which relies significantly on local agricultural produce to fulfil local needs for vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an early study by Dulymamode et al [18] reported that over 200 taxa were identified on the island, of which 90% were new records that had been assigned to one genus and 38 new species. However, studies that specifically focus on Fusarium species are severely lacking, with the only work being a 2023 study by Mamode Ally et al [19] who reported the first case of Fusarium acacia-mearnsii responsible for leaf blight in pumpkin in Mauritius. This highlights the need to undertake more research on the prevalence of Fusarium species in the country as an outbreak of Fusarium infection could have devastating consequences for Mauritius, which relies significantly on local agricultural produce to fulfil local needs for vegetables.…”
Section: Introductionmentioning
confidence: 99%